Anthony Paraskeva. Samuel Beckett and Cinema. London: Bloomsbury, 2017. - Katarzyna Peric (Studies in 20th & 21st Century Literature, 2018)
Review of Anthony Paraskeva. Samuel Beckett and Cinema. London: Bloomsbury, 2017. 195 pp.
Keywords: Beckett; cinema; modernism